Promotion of Street-Dance Training on the Executive Function in Preschool Children - Shen, Yue; Zhao, Qing; Huang, Yue; Liu, Ge; Fang, Lele (Frontiers in Psychology, 2020)
Executive function is the center of cognitive function, emotional function, and social function, and plays an important role in children's cognitive development. Previous studies used music, sports, and other training methods to promote the development of children's executive function. but researchers are still exploring more comprehensive and effective training methods. Street-dance, as a comprehensive dance form integrating the characteristics of movement, music, rhythm, and so on, needs the coordination of individual sensory systems and a sense of musical rhythm and action. These are the same activity elements found in previous studies that can improve the individual executive function of children. In order to investigate the promoting effect of street-dance training on children's executive function, this study designed a street-dance training program integrating the characteristics of each component of executive function. Sixty preschool children around the age of four (M=52.4, SD=3.95) participated using the pretest-posttest experimental design. The dancing group conducted street-dance training 3 times a week, 40-50 minutes each time for a total of 24 times; the control group did not train. We discovered that eight weeks of street-dance training can promote the development of executive function in preschool children, and we discussed about the potential mechanism of the street dance training effects and the implications of intervention programs.